HUBUNGAN POWER OTOT LENGAN DAN BAHU TERHADAP HASIL PUKULAN BACKHAND PADA ATLET TENIS MEJA JUNIOR PUTRA CLUB MALAY SPORT PEKANBARU - Dalilla, Ilham; Slamet, Slamet; Nita Wijayanti, Ni Putu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is "Strength of arm muscle and shoulder with backhand punch at junior athlete athlete of club son malay sport Pekanbaru?", So that the future of the athlete can perform much better and play again and the most important after research and know how much athletic ability to execute backhand punch to improve in advance to compensate for the opponent's game and maximize performance in the future. The form of this study is (correlation), with a population of table tennis player club Malay Sport Pekanbaru. the data in this study are the complete population of 6 people. The instrument used in this study is a second-hand polishing handball with a return stroke, which measures the muscular strength of the arms and shoulders and measures the results of the blows of the backhand drive. Thereafter, data were statistically processed, to test the normality using lilifors test at a significant level of 0.05α. The proposed hypothesis is that there is a significant relationship between arm and shoulder muscle strength compared to the results of the backhand punch. Based on the analysis of normality test yield Lhitung equal to 0.2462 and Ltabel 0.319, average Lhitung <Ltabel. Based on the analysis of statistical data, there is an average variable X 3.30 and the average variable Y of 44.5, then the data is normally distributed. So there is a link between arm and shoulder muscle strength against backhand loops on junior athlete athletes son club malaysport Pekanbaru.Keywords: Powerful muscle arm and shoulder, Backhandpons